Mediating role of international entrepreneurial orientation in the relationship between innovativeness and networks on internationalization of SMEs in Nigeria - Karage, Ahmed Ibrahim (2019)
Innovativeness and network are arguably important factors that are associated with a firm internationalization. There is an increase in the body of literature on the role of innovativeness and network on a successful internationalization of SMEs. However, research on domestic and international perspectives of firm innovativeness and network in a single framework to ascertain their impacts on the SMEs internationalization remains scarce. Furthermore, the mediation effect of international entrepreneurial orientation (IEO) dimensions (Innovativeness, Pro-activeness and Risk-taking) on the above relationship has a strong appeal but lacks empirical support. Likewise, what is not yet clear is the moderation effect of export promotion program on the association between international entrepreneurial orientation and the internationalization of SMEs. Given the above motivation, the study developed a conceptual framework based on dynamic capability view and supported by internationalization theory to examine whether domestic innovativeness, international innovativeness, domestic network and international network influence the internationalization of SMEs in Nigeria. In addition, the study investigated the mediating effect of international entrepreneurial orientation on relationship between the antecedents and outcome and export promotion programs as contingence of the relationship between IEO and internationalization of SMEs. The study used Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS software version 3.2.7 and sample data collected from 266 Nigerian exporting SMEs. The results showed that domestic innovativeness and domestic network were statistically significant with medium to large effect sizes, albeit international innovativeness and international network were insignificant. These results support two out of the four hypotheses on direct relationships. The mediating effect of innovativeness and risk taking dimensions of IEO has been found to be significant, with small to medium effect sizes in the model. However, the moderation hypotheses have not been supported by the data collected for this study. The findings extend both empirical and theoretical literature on international entrepreneurship that has been underexplored. With these results, the researcher concludes that the study makes contribution to theory and practice. Direction for future study has been suggested based on the limitations identified in the study.